Adaptogenic flower buds exert cancer preventive effects by enhancing the SCFA-producers, strengthening the epithelial tight junction complex and immune responses. (September 2020) - Xia, Wenrui; Khan, Imran; Li, Xiao-ang; Huang, Guoxin; Yu, Zhiling; Leong, Wai Kit; Han, Ruixuan; Ho, Leung Tsun; Wendy Hsiao, W.L.
Graphical abstract: Abstract: Microbiome therapy has attracted a keen interest from both research and business sectors. Our lab has been applying this "second genome" platform to assess the functionality of herbal medicines with fulfilling results. In this study, we applied this platform to assess the potential cancer-preventive effects of three selected adaptogenic plants. The flower buds from these plants were used to constitute Preparations SL and FSP according to the receipts of two commonly consumed Chinese medicinal decoctions for gastrointestinal discomfort. Preparation SL contains Sophorae japonica and Lonicerae Japonicae, and Preparation FSP contains Sophorae japonica and Gardenia Jasminoides. SL and FSP extracts significantly (p < 0.001) lowered the polyp burden, as well as the expressions of oncogenic signaling molecules, such as MAPK/ERK, PI3K/AKT, and STAT3 in Apc Min/+ mice. The inflamed gut was alleviated by shifting M1 to M2 macrophage phenotypes and the associated immune cytokines. The other remarkable change was on the extracellular tight junction protein complex, where the occludin, ZO-1, ICAM-1, E-cadherin were significantly (p < 0.05) upregulated while the N-cadherin and β-catenin were downregulated in the treated mice. The above physiological changes in the gut epithelial barrier were companied with the changes in gut microbiome. The 16S Sequencing data revealed a marked decrease in the potential pathogens (especially Helicobacter species and hydrogen sulfide producing-bacteria) and the increase in beneficial bacteria (especially for species from the genera of Akkermansia, Barnesiella, Coprococcus, Lachnoclostridium, and Ruminococcus ). The majority of which were the short-chain fatty acids (SCFAs) producers. Meanwhile SCFAs-sensing G protein-coupled receptors (GPCRs), including GPR41, GPR43, and GPR109a were also significantly upregulated. In a recent report, we proved that the bacteria-derived SCFAs plays an essential role to the anti-cancer effects of the mushroom polysaccharides and saponins in Apc Min/+ mice. In this study, we further demonstrated that butyrate treatment could enhance the extracellular tight junction protein complex as effective as the treatments with SL and FSP to the Apc Min/+ mice. Our findings provide strong evidence of the vital role of the SCFA-producers and their metabolites to the cancer-preventive properties of the SL and FSP preparations.